The Transition from International Schools to Higher Education: Educational Biographies of Young Graduates from International Schools in the Lisbon Region - Schippling, A. (ECER 2021 - The European Conference on Educational Research, 2021)
The field of international education, especially the segment of international schools that are regulated by transnational educational organisations such as the International Baccalaureate®, has grown significantly in recent decades. At the same time, a diversification of models of international education can be observed as the school population is changing (e.g. Ball & Nikita, 2014). In Portugal these development tendencies can also be observed, even if the increase is more modest, especially in the Lisbon region (Schippling & Abrantes, 2018). For Portugal a research deficit on studies on international schools can be identified. There are some studies related to the field of international schools (e.g. Macedo & Araújo, 2016; Louçã et al., 2014; Schippling & Abrantes, 2018), but research on the perspective of school actors is scarce (e.g. Schippling, 2018). This contribution responds to this research deficit and presents the first results of an analysis of educational biographies of young graduates from three international schools, representing different models in international education in the Lisbon region (Schippling & Abrantes, 2018, pp. 20-22).(1) There will be a focus on the question of how the transition of graduates of international schools to the field of higher education takes place and how they perceive this transition (e.g. Krüger et al., 2019): a question hitherto unanalysed in the Portuguese context. The study combines theoretical elements from critical research on elites such as the theory of habitus (e.g. Bourdieu, 1989) and its development in the context of biographical research (e.g. Lahire, 1998; Abrantes, 2013; Helsper et al., 2014) with concepts from research on transnationalisation that have been developed in the context of school research and research on youth (e.g. Schippling & Keßler, 2021). These are, for example, concepts such as ‘transnational spaces of education’ (e.g. Hayden, 2011) or ‘transnational/cosmopolitan capital’ (e.g. Weenink, 2008; Kenway & Koh, 2013) that were developed as a reaction to a lack of tools on a theoretical and also methodological level for researching international education (Resnik, 2012, p. 292). (1) The contribution is based on a postdoctoral research project entitled “The internationalisation of elite education in Portugal. A qualitative study on international schools in Greater Lisbon” (CIES-Iscte, Lisbon; Martin-Luther-University Halle-Wittenberg) and funded by the Foundation of Science and Technology (FCT). Methodology The contribution is based on a qualitative empirical research design that focuses on analysis of interviews about the educational biography of graduates from three international schools in the Greater Lisbon region. The students were interviewed until up to two years after their transition to national or international universities or other higher education institutions; professional life or other trajectories. In total, 13 interviews were carried out: 7 interviews with graduates from an IB World School, 4 interviews with graduates from a traditional school abroad and 2 interviews with graduates from a Portuguese School with an international profile (Cambridge Assessment International Education). The interviews had an open structure and comprised aspects as school choice, experiences in school, transition to universities/professional life/other trajectories, family influences, peer influences, international mobility, orientations related to inter/transnationality etc.). For reasons associated with COVID-19, and also because of the international mobility of many graduates, the interviews were conducted online, which implied new methodical challenges. The analysis of the interviews is conducted using the documentary interpretation method (e.g. Bohnsack, 2010), a reconstructive empirical method that was also developed for biographical analysis (e.g. Nohl, 2012). Conclusions The contribution responds firstly to a deficit of research on international education in Portugal, which is especially concentrated on the microperspective of school actors (Schippling, 2018). It is the first study which analyses educational biographies of students from international schools in Portugal. Secondly, the contribution opens the Bourdieusian critical theory of elite (education) for researching transnational phenomena in education, in this case taking the example of educational biographies of international mobile students. In this context, the contribution also is an invitation to reflect on the adequacy of the paradigm of methodological nationalism (e.g., Beck, 2007), which characterises the Bourdieusian theory (Kenway & Koh, 2013, p. 287), for studying international education. Oriented to overcoming the paradigm of methodological nationalism in biographical research, the third contribution of the study is in developing adequate methodical/methodological tools for researching inter/transnational contexts in education. In conclusion, the contribution not only responds to a lack of research on international education in Portugal but also develops reflection on the theoretical and methodological level based on overcoming the paradigm of methodological nationalism that is crucial for carrying out cross-cultural research in education. References: Abrantes, P. (2013). A escola da vida. Socialização e biografia(s) da classe trabalhadora. Lisboa: Mundos Sociais. Ball, S., & Nikita, D. (2014). The global middle class and school choice: A cosmopolitan sociology. Zeitschrift für Erziehungswissenschaft, 17(3), 81-93. Beck, U. (2007). The cosmopolitan condition. Why methodological nationalism fails. Theory, Culture and Society, 24(7-8), 286-290. Bohnsack, R. (2010). Rekonstruktive Sozialforschung. Einführung in qualitative Methoden. Opladen/Farmington Hills: Barbara Budrich. Bourdieu, P. (1989). La noblesse d'état. Paris: Éditions de Minuit. Hayden, M. (2011). Transnational spaces of education: the growth of the international school sector. Globalisation, societies and education, 9(2), 211-224. Helsper, W., Kramer, R.-T., & Thiersch, S. (2014). Schülerhabitus. Theoretische und empirische Analysen zum Bourdieuschen Theorem der kulturellen Passung. Wiesbaden: Springer VS. Kenway, J., & Koh, A. (2013). The elite school as ‘cognitive machine’ and ‘social paradise’: Developing transnational capitals for the national ‘field of power’. Journal of Sociology, 43(2-3), 272-290. Krüger, H.-H., Hüfner, K., Keßler, C. I., Kreuz, S., Leinhos, P., & Winter, D. (Eds.). (2019). Exklusive Bildungskarrieren von Jugendlichen und ihre Peers am Übergang in Hochschule und Beruf. Wiesbaden: Springer VS. Lahire, B. (1998). L'homme pluriel. Les ressorts de l'action. Paris: Nathan. Louçã, F., Lopes, J. T., & Costa, J. (2014). Os burgueses. Lisboa: Bertrand Editora. Macedo, E, & Araújo, H. C. (2016). Can geographies of privilege and oppression combine? Elite education in Northern Portugal. In A. Koh, & J. Kenway (Eds.), Elite schools: Multiple geographies of privilege (pp. 157-170). London: Routledge. Nohl, A.-M. (2012). Interview und dokumentarische Methode? Anleitungen für die Forschungspraxis. Wiesbaden: VS Verlag für Sozialwissenschaften. Resnik, J. (2012). Sociology of international education – an emerging field of research. International studies in Sociology of Education, 22(4), 291-310. Schippling, A. (2018). Researching international schools: Challenges for comparative educational research. Revista Lusófona de Educação, 41(41), 193-204. Schippling, A., & Abrantes, P. (2018). Para uma visão panorâmica do campo das escolas internacionais na Grande Lisboa. Educação, Sociedade & Culturas, 52, 7-27. Schippling, A., & Keßler, C. I. (2021; in print). Transnationale Perspektiven in der Kindheits- und Jugendforschung. In H.-H. Krüger, C. Grunert & K. Ludwig (Eds.), Handbuch Kindheits- und Jugendforschung. Wiesbaden: Springer VS. Weenink, D. (2008). Cosmopolitanism as a form of capital: parents preparing their children for a globalising world. Sociology, 42(6), 1089-1106.